Active radiation detectors for use in space beyond low earth orbit: spatial and energy resolution requirements and methods for heavy ion charge classification - McBeth, Rafe A., author; Borak, Thomas, advisor; Brandl, Alexander, committee member; Ray, Andrew, committee member; Homrighausen, Darren, committee member (Colorado State University. Libraries, 2017)
Space radiation exposure to astronauts will need to be carefully monitored on future missions beyond low earth orbit. NASA has proposed an updated radiation risk framework that takes into account a significant amount of radiobiological and heavy ion track structure information. These models require active radiation detection systems to measure the energy and ion charge Z. However, current radiation detection systems cannot meet these demands. The aim of this study was to investigate several topics that will help next generation detection systems meet the NASA objectives. Specifically, this work investigates the required spatial resolution to avoid coincident events in a detector, the effects of energy straggling and conversion of dose from silicon to water, and methods for ion identification (Z) using machine learning. The main results of this dissertation are as follows: 1. Spatial resolution on the order of 0.1 cm is required for active space radiation detectors to have high confidence in identifying individual particles, i.e., to eliminate coincident events. 2. Energy resolution of a detector system will be limited by energy straggling effects and the conversion of dose in silicon to dose in biological tissue (water). 3. Machine learning methods show strong promise for identification of ion charge (Z) with simple detector designs.